EXPERIMENTAL STUDY OF FURCATION AREA AND PROSPECTS OF ITS COMPLEX TREATMENT - Yu.V. Sidash; O.P. Kostyrenko; V.N. Petrushanko (Український стоматологічний альманах)
Relevance. The issue of quality endodontic treatment of teeth with complicated caries is still known as requiring thoughtful research. A significant percentage of periodontitis occurs in the area of furcations of multi-rooted teeth, sometimes alone, but more often as combined with apical periodontitis. Among the number of unsolved tasks, there is question about furcation areas and in particularly their antiseptic treatment and obturation in the complex treatment of chronic apical periodontitis of multi-rooted teeth.